Jury review - Mohamad, Abdul Latiff; Abd Ghani, Idris; Juraimi, Abdul Shukor (Universiti Putra Malaysia Press, 2013)
The spirit of the vast rainforest in Malaysia as well as in many other tropical countries is harboured by the unknown diversity and varied functions of its small but important and dominant inhabitants, the insects. All of us are very familiar with insects as they seem to be the most common form of wildlife even in the forests and in urban areas.